(untitled) (SAARC Journal of Agriculture, 2022)
Rice (Oryza sativa L.) is one of the main cereal crops in the world and the main staple food of Bangladesh. Amylose content of rice endosperm is the main chemical properties that contributes the eating and cooking quality. On the other hand, rice protein is the important source of nutrition of almost 50 per cent of the world’s population living on rice. A total of 12 rice genotypes including ten advanced mutant lines, one landrace namely Laxmidigha along with BRRI dhan49 was collected from Plant Breeding Division of Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh and Bangladesh Rice Research Institute (BRRI), Gazipur. The genotypes were analyzed to assess the amylose and protein content as well as their genetic diversity relationship. Among all the tested genotypes amylose content were ranged from 23.9-20.3% where highest amylose percentage was found for Magic-86 (25.6%). Protein content of the genotypes were ranged from 8.50-5.04%, where highest 8.86% protein was recorded for SSB-3. The highest gene diversity (0.81) was observed in RM519 marker and the lowest (0.28) was in RM111 marker. The PIC values ranged from 0.24-0.78 with a mean of 0.51. The highest Nei’s genetic distance value 0.87 was found in RM-16(N)-10 vs RM-40(C)-4-2-8 and the lowest value 0.18 was found in LD-200-1-3-3-8 vs LD-200-1-3-2-4. A dendogram was constructed using UPGMA system based on Nei’s similarity coefficient and six major clusters were obtained at 0.7 cut off. The genotypes showing diverse ranges of amylose and protein content tended to cluster together in the dendogram with some exceptions. SAARC J. Agric., 20(1): 41-53 (2022)